Preoperative assessment using a scoring system after neoadjuvant chemotherapy with docetaxel, cisplatin, and 5-fluorouracil for locally advanced esophageal cancer: Who can avoid surgery? - Yasunori Kurahashi; Toshihiko Tomita; Takuya Okugawa; Kazuhiro Kitajima; Motoki Murakami; Shugo Kohno; Yudai Hojo; Eiichiro Nakao; Tatsuro Nakamura; Yoshinori Ishida; Shinichiro Shinzaki; Hisashi Shinohara (PLoS ONE, 2025)
Neoadjuvant chemotherapy (NAC) with docetaxel, cisplatin, and 5-fluorouracil (DCF) is highly effective for advanced esophageal squamous cell carcinoma, and patients with a good response sometimes desire to avoid surgery. The aim of this single-center, retrospective study was to predict the probability of residual tumors using a newly devised scoring system and identify conditions that may obviate the need for surgery. Between January 2017 and March 2024, 106 patients received NAC with DCF, followed by radical resection at our institution. After NAC, patients underwent multimodal assessments to correlate the evaluation parameters with residual tumors. A scoring system was developed by incorporating the parameters that exhibited significant differences. After calculating the scores for all patients, a receiver operating characteristic (ROC) curve was generated to determine the optimal cutoff value for predicting residual tumors. Eighteen patients achieved a pathological complete response, of whom 12 showed complete tumor disappearance, including lymph node metastases. The scoring system included the following seven parameters: endoscopic irregularity, elevation, and pink-color sign after iodine staining; identification of the main tumor, regional lymph nodes ≥5 mm in long diameter, presence of positive lymph node findings on computed tomography; and positive 18F-fluorodeoxyglucose uptake on positron emission tomography. The area under the ROC curve was 0.957, with a cutoff value of 3 for residual tumors. All patients with a score of 0 showed complete tumor disappearance. Our scoring system suggests that surgery might be safely omitted in patients with a score of 0. Comprehensive and flexible clinical decision-making is essential.